Manejo da fertirrigação para melancia em função da condutividade elétrica da solução do solo - Bardiviesso, Diógenes Martins [UNESP] (2015)
This work was carried in the agricultural production sector at Unidade Universitária de Cassilândia (Casilandia University Unit) - MS, Universidade Estadual de Mato Grosso do Sul (UEMS), in order to evaluate watermelon production due to the management of fertigation aiming to reach different electrical soil conductivity (0,6; 1,2; 1,8; 2,4; 3,0 e 3,6 dS m-1). Two experiments were performed (I and II) in May and September 2014, through randomized block design with six treatments (electrical conductivity of the soil solution) and four replications. Each portion was composed by two rows of eight meters with ten plants each. The available portion was constituted of eight central plants in each line. pH Analyses, electrical conductivity, N- NH4 +, N- NO3 - and K+ were performed in the soil solution collected during the crop cycle. Foliar analysis and measuring of the color intensity of green sheets were accomplished as well. In relation to production traits, length and fruit diameter, thickness of the peel, pH, soluble solids content (SS), titratable acidity (TA) and SS / TA ratio of the fruit pulp, number of fruits, total and commercial productivity of watermelon fruits were evaluated. The electrical conductivity of the soil solution was effective and it had a relevant role in discriminating treatments for fertigation management. It is recommended electrical conductivity of the soil solution in 2.0 dS m-1 for planting in May and 2.5 dS m-1 for planting in September